Carboniferous mafic-ultramafic intrusions in the Eastern Pontides (Pulur Complex): implications for the source of coeval voluminous granites - Topuz, Gültekin; Altherr, Rainer; Candan, Osman; Wang, Jia-Min; Okay, Aral I.; Wu, Fu-Yuan; Ergen, Ali; Zack, Thomas; Siebel, Wolfgang; Shangh, Cosmas K.; Schwarz, Winfried H.; Meyer, Hans-Peter; et al. (Lithos, 2023)
This study deals with the age and petrogenesis of mafic-ultramafic intrusions ranging in size from a few meters to 10 km within the Early Carboniferous high-grade gneisses of the Pulur Complex in the Eastern Pontides. The intrusions comprise dunite, wehrlite, gabbronorite, leucogabbro, anorthosite and ilmenite-bearing gabbronorite of cumulus origin, and are crosscut by dikes of ilmenite-bearing gabbronorite, leucogranite and microdiorite. U-Pb dating on zircons from gabbronorite, anorthosite and leucogranite yielded igneous crystallization ages of 322-326 Ma, indicating that the intrusions were emplaced ca. 5-7 Ma after the peak of high-grade metamorphism, and form part of the Late Carboniferous high-volume magmatism in the region. In most cumulate rocks, Cr-Al spinel, olivine and plagioclase were early crystallizing phases, followed by orthopyroxene, clinopyroxene and hornblende. Whole rock geochemical data suggest that wehrlite, gabbronorite, leucogabbro and anorthosite stem from a common magma, and ilmenite-bearing gabbronorite and dikes of leucogranite and microdiorite from different magmas. Application of mineral/melt partition coefficients to trace element compositions of clinopyroxene and hornblende in cumulate rocks suggests that the main cumulate body was derived from middle- to high-K calc-alkaline basic melts, and relatively late ilmenite-bearing gabbronorites from hypersthene-normative Ca-rich melts. All the rock types display radiogenic Sr and Pb isotopic signatures, and unradiogenic Nd isotopic ratios, which are indistinguishable from those of the coeval voluminous high-K calc-alkaline I-type granites in the region; the isotopic ratios are probably related to the metasomatism of the lithospheric mantle by sediment-derived melts. We suggest that the parental melts of the mafic-ultramafic intrusions and those of the high-K calc-alkaline granites were genetically related, and melts of the high-K calc-alkaline granites were probably derived from the melting of newly underplated calc-alkaline basic material at lower crustal depths, that were compositionally comparable to the parental magmas of the mafic-ultramafic intrusions.
Online verfügbar: 18. November 2022, Artikelversion: 24. November 2022
Gesehen am 15.08.2023